Photo release of nitrous oxide from the hyponitrite ion studied by infrared spectroscopy. Evidence for the generation of a cobalt-N2O complex. Experimental and DFT calculations - Chacón Villalba, Elizabeth (2017)
The solid state photolysis of sodium, silver and thallium hyponitrite (M 2 N 2 O 2 , M = Na, Ag, Tl) salts and abinuclear complex of cobalt bridged by hyponitrite ([Co(NH 3 ) 5 -N(O)-NO-Co(NH 3 ) 5 ] 4+ ) were studied by irradi-ation with visible and UV light in the electronic absorption region. The UV?visible spectra for free hyponitrite ionand binuclear complex of cobalt were interpreted in terms of Density Functional Theory calculations in order toexplain photolysis behavior.The photolysis of each compound depends selectively on the irradiation wavelength. Irradiation with340?460 nm light and with the 488 nm laser line generates photolysis only in silver and thalliumhyponitrite salts, while 253.7 nm light photolyzed all the studied compounds.Infrared spectroscopy was used to follow the photolysis process and to identify the generated products. Remark-ably, gaseous N 2 O was detected after photolysis in the infrared spectra of sodium, silver, and thallium hyponitriteKBr pellets. The spectra for [Co(NH 3 ) 5 -N(O)-NO-Co(NH 3 ) 5 ] 4+ suggest that one cobalt ion remains bonded to N 2 Ofrom which the generation of a [(NH 3 ) 5 CoNNO] +3 complex is inferred. Density Functional Theory (DFT) basedcalculations confirm the stability of this last complex and provide the theoretical data which are used in the in-terpretation of the electronic spectra of the hyponitrite ion and the cobalt binuclear complex and thus in the elu-cidation of their photolysis behavior.Carbonate ion is also detected after photolysis in all studied compounds, presumably due to the reaction of atmo-spheric CO 2 with the microcrystal surface reaction products. Kinetic measurements for the photolysis of thebinuclear complex suggest a first order law for the intensity decay of the hyponitrite IR bands and for the inten-sity increase in the N 2 O generation. Predicted and experimental data are in very good agreement.